Evaluasi Peran Perbankan Syariah terhadap Ketahanan Ekonomi Global Pasca Krisis Finansial - Nona Azzahra Nasution; Muhammad Alvin Novanda (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to evaluate the role of Islamic banking in strengthening global economic resilience after the financial crisis. The study emphasizes how the principles of risk-sharing, prohibition of speculative activities (gharar), and avoidance of interest (riba) in Islamic finance provide stability compared to the conventional interest-based system. The research adopts a qualitative approach through literature review and comparative analysis of financial data from international institutions such as the IMF and the Islamic Development Bank (IsDB). The findings reveal that Islamic banking contributes to reducing systemic risk by promoting asset-backed financing and ethical investment principles. Post-crisis recovery in several Muslim-majority countries shows that Sharia-based financial institutions maintain better liquidity and solvency ratios. The study concludes that the integration of Sharia-compliant mechanisms can serve as an alternative model for sustainable and crisis-resilient global finance.